Enhancement Of Salt Quality with Recrystallization Method from Crude Salt Raw Material on a Laboratory Scale - Joko Suryadi; Saifa Haikal Witcaksono; Putri Widad Salsabila; Eko Andrijanto; Yohana Fransiska Ferawati; Retno Dwi Jayanti; Kardian Rinaldi; Haryadi Haryadi (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Indonesia has significant maritime potential, particularly in salt production. However, national salt production has not yet met domestic demand, especially for industrial-grade salt, which requires a minimum NaCl content of 97%. Crude salt produced using traditional methods often contains only 88-94% NaCl and includes impurities such as Ca, Mg, and sulfate. This research aims to produce recrystallized salt that meets industrial standards and to determine the optimal conditions in a laboratory-scale simulator. The experimental method was conducted by simulating evaporation on a recrystallization table. Salt solutions were prepared from crude salt with varied concentrations of 22%, 25%, and 30%. The observed parameters included solution density, evaporation rate, and the content of NaCl, total hardness, and sulfate in the salt product. The results showed that recrystallization significantly increased the NaCl content and reduced impurities. Optimal conditions were achieved with a 22% salt solution, where crystal formation produced recrystallized salt with an NaCl content of 99.33%, total hardness of 0.47%, and sulfate content of 8.56 ppm. This quality has the potential to meet industrial salt standards. This study can serve as a reference for industrial salt production on a larger scale.